PENGARUH KECERDASAN INTELEKTUAL, BUDAYA ORGANISASI DAN FASILITAS KERJA TERHADAP KINERJA GURU SMA NEGERI 5 PURWOKERTO - Haryani; Cahyaningtyas R.U (Majalah Imiah Manajemen & Bisnis, 2020)
This research entitled "The Influence of Intellectual Intelligence, Organizational Culture and Work Facilities on Teacher Performance of SMA 5 Purwokerto". The purpose of this research was to analyze the effect of intellectual intelligence on the performance of teachers at Purwokerto Public High School 5, to analyze the influence of organizational culture on the performance of teachers at SMA 5 Purwokerto and to analyze the influence of work facilities on the performance of teachers at SMA 5 Purwokerto. The analysis uses multiple linear regression. From this research it can be concluded: The hypothesis that intellectual intelligence has a effect on the performance of teachers at SMA 5 Purwokerto, with a confidence rate of 95%, is accepted. This is evidenced by the t test which proves that the t count of intellectual intelligence is greater than t table (2,217> 2,0262). The hypothesis that organizational culture has a effect on the performance of teachers at SMA 5 Purwokerto, with a 95% confidence score, is accepted. This is evidenced by the t test which proves that t counts the organizational culture is greater than t table (2.600> 2.0262). The hypothesis which states that work facilities have a effect on the performance of teachers at SMA 5 Purwokerto, with a confidence rate of 95%, is accepted. This is evidenced by the t test which proves that t work facility count is greater than t table (2,313> 2,0262).